A connection between the consumer theory and quantity theory of money: a Cantillon’s approach - Moreira, Tito Belchior S. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
This essay shows a connection between consumer theory and quantity theory of money, inspired by Richard Cantillon's approach, in which changes in the money stock influence price levels, characterizing the elasticity of the money supply in relation to the price level to the consumer. Thus, changes in the money supply generate changes in the price level, and such monetary effects impact the consumer's optimal choice if the change in the money supply influences the prices of two goods with different intensities. When the government expands the amount of money in the economy, it affects relative prices and, consequently, changes the decisions of economic agents in a market economy. Based on US quarterly data, 1946:04 to 2019:04, the empirical results show that the change in the stock of money directly affects the optimal change in consumption and indirectly affects the optimal change in consumption via the change in relative prices, showing that money does not it's neutral.